Glossary for Lesson 27: Combining Functions


Composite Function

Given two functions, we can create a composite function by using the output of one of the functions as the input of the other function. If we have two functions named f and g , then we could combine them to create the composite functions f(g(x)) and g(f(x)) .  These can also be denoted as (f\circ g)(x) and (g\circ f)(x) , respectively.  For example, if f(x)=3x-2 and g(x)=x^3 , then (f\circ g)(x)=3x^3-2 , and (g\circ f)(x)=(3x-2)^3 .